Africanized honeybees in urban areas: a public health concern - Zaluski, Rodrigo; Kadri, Samir Moura; Souza, Edison Antonio De; Silva, Valdinei Moraes Campanucci Da; Silva, Juliane Reis Campanucci Da; Rodrigues-orsi, Patricia; Orsi, Ricardo de Oliveira [UNESP] (Sociedade Brasileira de Medicina Tropical - SBMT, 2014)
Introduction This study aimed to investigate the occurrence of Africanized honeybees in Botucatu, São Paulo, Brazil, and to implement a program to remove such swarms. Methods The occurrences of Africanized honeybee swarms between 2010 and 2012 were studied and strategies to prevent accidents were developed. Results We noted 1,164 cases of Africanized honeybee occurrences in the city, and 422 swarms were collected. The developed strategies to prevent accidents were disseminated to the population. Conclusions We contributed to reducing the risks represented by Africanized honeybee swarms in urban areas, by collecting swarms and disseminating strategic information for preventing accidents.
Keywords: Accident prevention; Apis mellifera; Urban areas